1992
DOI: 10.1002/ijc.2910500221
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of azoxymethane‐induced experimental colon carcinogenesis in wistar rats by 6‐hydroxydopamine

Abstract: The effects of 6-hydroxydopamine (6-OHDA) on the incidence, number and histology of colon tumors induced by azoxymethane (AOM), and on norepinephrine (NE) concentration in the colon wall and the labelling index of the colon mucosa were investigated in Wistar rats. Rats received sub-cutaneous (s.c.) injections of AOM once a week for 10 weeks, and throughout 35 weeks were also given intraperitoneal (i.p.) injections of 6-OHDA. Prolonged administration of 6-OHDA was found to cause a significant reduction in the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0
1

Year Published

1997
1997
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 26 publications
0
13
0
1
Order By: Relevance
“…9 I now describe in greater detail the aforementioned 7 lines of evidence that support an etiological role for NE in some types of cancer. The first line of evidence has been put forth primarily by a group of researchers in Japan during the last several decades, [11][12][13][14][15][16][17][18][19][20] as well as by some Russian scientists [21][22][23] and others. 24,25 This line indicates that in rodents the level of NE, or degree of activation of adrenoceptors with drugs, in certain bodily tissues correlates with the degree of tumorigenesis in those tissues.…”
Section: Literature Search Detailsmentioning
confidence: 99%
See 2 more Smart Citations
“…9 I now describe in greater detail the aforementioned 7 lines of evidence that support an etiological role for NE in some types of cancer. The first line of evidence has been put forth primarily by a group of researchers in Japan during the last several decades, [11][12][13][14][15][16][17][18][19][20] as well as by some Russian scientists [21][22][23] and others. 24,25 This line indicates that in rodents the level of NE, or degree of activation of adrenoceptors with drugs, in certain bodily tissues correlates with the degree of tumorigenesis in those tissues.…”
Section: Literature Search Detailsmentioning
confidence: 99%
“…24,25 This line indicates that in rodents the level of NE, or degree of activation of adrenoceptors with drugs, in certain bodily tissues correlates with the degree of tumorigenesis in those tissues. In particular, during chemically induced carcinogenesis, when the level of NE is increased with drugs such as bombesin 11,12 or the tricyclic antidepressant desipramine, 13 or a low protein diet, 14,15 tumorigenesis increases; when the level of NE is decreased with 6-hydroxydopamine, 16 phenylalanine, 17 or cysteamine, 18,19 tumorigenesis decreases. However, when the level of NE is decreased with clonidine, tumorigenesis is unaffected.…”
Section: Literature Search Detailsmentioning
confidence: 99%
See 1 more Smart Citation
“…depression associated with psychosomatic and somatic symptoms was seen in majority of patients with GIS diseases (Guldahl, 1977). Tatsuta et al (1989) reported that supression of sympathetic nervous system inhibits carcinogenesis while stimulation of sympathetic nervous system activity increases carcinogenesis (Tatsuta et al, 1989;1992). It's well known that main mechanism of action of antidepressant agents is oriented to increase noradrenergic, serotonergic and dopaminergic activity (Baldessarini, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…10 Previous findings indicate that increased sympathetic nervous system activity enhances the development of gastric cancers, and suppression of sympathetic nervous system activity inhibits carcinogenesis. 11,12 The role of catecholamines are important in different cancer types because of their regulatory effects on tumor angiogenesis, [13][14][15][16] which is critical for the growth and progression of malignant tumors. 17 Bromocriptine is a dopamine receptor agonist known to enhance gastric carcinogenesis induced by Nmethyl-N 0 -nitro-N-nitrosoguanidine (MNNG) in Wistar rats.…”
mentioning
confidence: 99%